Experimental and numerical studies on self-centring beam-to-column connections free from frame expansion. (1st November 2019) - Fang, Cheng; Wang, Wei; Feng, Weikang
Highlights: A new type of self-centring connections free from frame-expansion is presented. SMA ring spring-based devices are the kernel components of the connection. A proof-of-concept connection specimen is tested. An extensive parametric study is carried out. Design considerations are presented in an illustrative manner. Abstract: In this study, a new type of self-centring beam-to-column connection is proposed, which is free from frame expansion and therefore causes minimal damage to the slab system. The connection rotates about the top flange, with shape memory alloy (SMA) ring spring-based devices installed underneath the beam. An experimental investigation on a proof-of-concept connection specimen was first carried out, followed by a comprehensive numerical study looking at a variety of parameters that may affect the connection behaviour. The test specimen showed typical flag-shaped hysteretic response with excellent self-centring capability under both positive and negative moments. Moderate energy dissipation with an equivalent viscous damping ratio of up to 15% was exhibited. The subsequent numerical study revealed that the friction and precompression of the SMA ring spring system critically affect the overall connection behaviour. In addition, extra energy dissipation can be reliably provided by the web bolts, and a "partial self-centring" connection with fully tightened high-strength web bolts is recommended. The cover plate design and the influence of concrete slab were also discussed. Considering a prototype building frame, an illustrative connection design example was finally presented, with some preliminary design recommendations briefly outlined. The design example clearly demonstrates the feasibility of the proposed connection in a "full-scale" structure.